Assessment of three different drying technologies (sun, solar and bin) used for the production of cassava (manihot esculenta crants) chips in Ghana - Bentil, Benjamin (2011)
A thesis submitted to the School of Research and Graduate Studies, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the award of Master of Science (Msc. Postharvest Technology) degree